1997
DOI: 10.1002/(sici)1097-0215(19970317)70:6<722::aid-ijc15>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor and amphiregulin up‐regulate matrix metalloproteinase‐9 (MMP‐9) in human breast cancer cells

Abstract: The EGF family of proteins encompasses several polypeptides such as epidermal growth factor (EGF), transforming growth factor alpha (TGFa), amphiregulin (AR) and heregulin (HRG-b1). These polypeptides regulate proliferation in breast cancer cells through interaction with membrane receptors. It has been previously shown that high EGF receptor number correlates with aggressive behavior and increased metastasis in human breast cancer. In the present study, we investigated the association between EGF and EGF-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 0 publications
2
73
0
Order By: Relevance
“…Moreover, the ratio PAi-1/uPA appeared clearly in favour of PAi-1, suggesting that uPA activity might be efficiently neutralized. Recently, studies have demonstrated that EGF and AR were able to induce the expression of matrix metalloproteinases (MPPs) in a variety of tumoral cell lines (Kondapaka et al, 1997;Sundareshan et al, 1999). Although these studies have not established a direct link between the increased production of MMPS and cell invasiveness, we suggest that EGF and AR might modulate invasion of MCF-7 cells by up-regulating the expression of member(s) of MPP family.…”
Section: Mda-mb231 Mcf-7mentioning
confidence: 68%
“…Moreover, the ratio PAi-1/uPA appeared clearly in favour of PAi-1, suggesting that uPA activity might be efficiently neutralized. Recently, studies have demonstrated that EGF and AR were able to induce the expression of matrix metalloproteinases (MPPs) in a variety of tumoral cell lines (Kondapaka et al, 1997;Sundareshan et al, 1999). Although these studies have not established a direct link between the increased production of MMPS and cell invasiveness, we suggest that EGF and AR might modulate invasion of MCF-7 cells by up-regulating the expression of member(s) of MPP family.…”
Section: Mda-mb231 Mcf-7mentioning
confidence: 68%
“…Immunoblots were performed as described previously (Kondapaka et al, 1997) by standard methods on crude protein extracts obtained from 5610 6 cells untreated or treated. Cell extracts containing 50 mg of total protein per sample (determined by using Sigma protein assay) were analysed by SDS ± PAGE using 12% polyacrylamide gels or as indicated.…”
Section: Immunoprecipitation and Immunoblot Analysismentioning
confidence: 99%
“…Equal amount of protein from di erent groups were subjected to SDS ± PAGE and transferred to a membrane. Phosphorylated MAPK and total MAPK were assayed as described previously (Kondapaka et al, 1997). In brief the activated proteins were detected by immunoblot analysis with the phospho-MAPK.…”
Section: Western Blot Analysis Of Mapkmentioning
confidence: 99%